Makro Akuntansi dalam Menjelaskan Krisis Biaya Hidup: Peran Mediasi Kebijakan Upah Minimum Regional - Yusron Difinubun; Alyn wulandary; Musriani Musriani (Program Studi Akuntansi Unimuda Sorong, 2025)
Purpose: This study analyzes the effects of money supply, oil price increases, and the COVID-19 pandemic on the Cost of Living Crisis through the mediating role of Regional Minimum Wage (RMW) in Sorong City using a Public Macro Accounting perspective. Methodology/approach: An exploratory sequential mixed-method design was employed. Qualitative data were obtained through interviews with 17 informants across six districts, while quantitative data were collected from 397 respondents using structured questionnaires. Data were analyzed using the Miles and Huberman qualitative analysis model and Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The results indicate that money supply and oil price increases have positive and significant effects on the Cost of Living Crisis. The COVID-19 pandemic does not have a significant direct effect, although it significantly influences the crisis indirectly through Regional Minimum Wage. Regional Minimum Wage significantly affects the Cost of Living Crisis and successfully mediates the relationships between money supply, oil price increases, and the COVID-19 pandemic with the Cost of Living Crisis. Practical implications: The findings provide empirical evidence for policymakers to strengthen wage-setting policies, inflation control, and regional economic resilience, particularly in eastern Indonesia. Originality/value: This study contributes to Public Macro Accounting literature by positioning Regional Minimum Wage as a policy transmission mechanism linking macroeconomic variables to the Cost of Living Crisis in an underexplored regional context.